Pesantren Resistance to Modern Education System and It’s Implication to Culture of Learning: a Study on Pondok Pesantren Al-Is'af Kalabaan, Guluk-Guluk, Sumenep, Jawa Timur - Solichin, Mohammad Muchlis (LPPM IAIN Kudus, 2019)
Pesantren (Islamic boarding school) grew as traditional Islamic education institutions since the beginning of Islam arrival to Indonesia. The kiai in the traditional pesantren educated the student set of classical Islamic text books those organized by the method sorogan and bandongan. In the early 20th century, pesantrens have got challenge with school education system that introduced by Dutch Colonial Government in the first 1900s. The challenge to pesantren also came from Muslim Reformist which also performed modern educational system in their schools and madrasah. Facing the challenge, most of pesantren modernized their educational system by performing schools and madrasah affiliated to the Indonesian government. There were only a few pesantrens those rejected the of modern educational system. Pesantren al- Is’af rejected the school education system and had ben keeping the sustainability of traditional education of Islamic knowledge teaching learning. The rejection brought about the effort of the pesantren in sthrengtening teaching learning classical Islamic textbook (kitab kuning) with sorogan and bandongan methods. Some of the text books had taugt the rule of santri learning. There were many rules, norms and belief that resulted the culture of learning in Pesantren.